Penerapan Business Model Canvas untuk Mengembangkan Strategi Bisnis ACW Studio - Susanto, Capriandika Putra; Widhiwipati, David Reza; Ramdani, Anka Luffi; Kuntari, Wien (FEB Universitas Maritim Semarang, 2024)
The development of digital technology has opened significant opportunities for the website development industry to innovate, particularly through the implementation of Augmented Reality (AR) technology. This study explores the application of the Business Model Canvas (BMC) in designing a business strategy for ACW Studio, a website development service company utilizing AR technology. By integrating AR, ACW Studio offers a unique value proposition, such as creating interactive websites and AR-based creative products, significantly enhancing customer experience. The use of BMC helps the company analyze nine key business elements, including strategic collaboration, service personalization, and optimization of digital distribution channels. The study results show that AR-based strategies can provide substantial competitive advantages in a highly competitive market while also opening opportunities for expansion into sectors such as education, retail, and tourism.